Relationship of the structure of coordinational preparation and stability of competitive activity of female rhythmic gymnastics athletes - Dveyrina O.A.; Viner I.A.; Terekhina R.N. (Theory and Practice of Physical Culture, 2024)
Objective of the study is to justify the introduction of new formats of cultural and sports events that ensure the growth of sports skills of gymnasts and allow, by taking into account the mechanism of interconnection of the structure of coordination readiness, to increase the stability of the competitive activity of female athletes in rhythmic gymnastics. Methods and structure of the study. At the first stage, the mechanism of the relationship between the structure of coordination readiness and the stability of competitive activity of female rhythmic gymnastics athletes was identified. At the second stage, new formats of cultural, sports and public events were introduced, ensuring the growth of the sports skills of gymnasts. The study was conducted during 2021-2024. on the basis of the sports complex «Irina Viner-Usmanova Gymnastics Palace». More than 300 athletes of various levels of preparedness were examined. Results and conclusions. Due to the variety of conditions formed by the specifics of the gala concert, unusual lighting and sound, different from those typical for educational, training and competitive events, athletes during rehearsals and, in fact, performances at the gala concert, had the opportunity to supplement the motor programs of the elements of competitive exercises with sensory ones. corrections that ensure the construction, coding and correction of movements of all limbs of the body relative to each other in the coordinate system of one’s own body.